أحكام الصورية في القانون المدني الجزائري - وحيدة بوكحيل; محمد عبد العزيز بن بو عبد الله (My University, 2022)
Summary: The motive has emerged as long ago as the Romans, not known to the Algerian legislature, nor to other Arab legislation. This has remained for jurists, who have agreed that it is a false act in order to conceal the truth. It appears in the form of a legal act that produces a prima facie act that conceals the true intent. It is considered a form of circumvention of the law. Contracts between contracting individuals can be abstract, but their purpose is as legitimate as the trusteeship in the trusteeship contract in order to avoid disputes between heirs or their purpose as unlawful as fraud or circumvention of the law. This type of contract, which raises disputes between contracting or other individuals, has made provisions for the adjudication of such disputes by Algerian legislation. The legislature confined itself to articles 198 and 199 of the Algerian Civil Code, which spoke of mock under the heading of securing creditors' rights. However, these articles face shortcomings and incapacity in the disputes before the courts, since they do not contain all the provisions requiring the judge to revert to and overturn general rules. ..................... الملخص: إن الصورية ظهرت قديما عرفها الرومان، لم يعرفها المشرع الجزائري، ولا التشريعات العربية الأخرى، وبقي ذلك للفقهاء فاتفقو على كونها تصرف كاذب من أجل إخفاء الحقيقة، حيث تظهر في شكل واقعة قانونية تنتج عمل ظاهري يخفي القصد الحقيقي، فهي تعتبر شكل من أشكال التحايل على القانون. فالعقود التي تبرم بين الأفراد المتعاقدين يمكن أن تكون صورية غير حقيقية لكن الهدف منها مشروع مثل الصورية في عقد الوصية وهذا لتفادي النزاع بين الورثة أو الهدف منها غير مشروع كالغش أو التحايل على القانون. وهذا النوع من العقود الذي يثير نزاعات بين الأفراد المتعاقدين أو الغير، قد وضع المشرع الجزائري أحكاما للفصل في هذه النزاعات. حيث إكتفى المشرع بالمادتين ، 198 ، 199 من القانون المدني الجزائري التي تتحدث عن الصورية تحت عنوان ضمان حق الدائنين، لكن هاتان المادتان تواجهان قصورا وعجزا أمام النزاعات المعروضة أمام القضاء كونها لم تنص على جميع الأحكام مما يستلزم على القاضي العودة إلى القواعد العامة وإسقاطها. .................... Résumé : Le motif est apparu il y a longtemps que les Romains, pas connu de la législature algérienne, ni d’autres lois arabes. Cela est resté pour les juristes, qui ont convenu que c’est un faux acte pour cacher la vérité. Il se présente sous la forme d’un acte juridique qui produit un acte prima facie qui dissimule l’intention véritable. Il est considéré comme une forme de contournement de la loi. Les contrats entre individus contractants peuvent être abstraits, mais leur but est aussi légitime que la tutelle dans le contrat de tutelle afin d’éviter les litiges entre héritiers ou leur but aussi illégal que la fraude ou le contournement de la loi. Ce type de contrat, qui soulève des litiges entre contractants ou autres personnes, a prévu l’arbitrage de ces litiges par la législation algérienne. Le législateur s’est limité aux articles 198 et 199 du Code civil algérien, qui parlaient de moquerie sous le titre de garantie des droits des créanciers. Cependant, ces articles font face à des lacunes et à une incapacité dans les litiges devant les tribunaux, car ils ne contiennent pas toutes les dispositions obligeant le juge à revenir aux règles générales et à les renverser.